Synthesis of Poly(N-vinyl-2-pyrrolidone-co-methyl methacrylate) by Maghnite-H+ a Non-toxic Catalyst - Mohamed Benadda; Mohamed Issam Ferrahi; Mohamed Belbachir (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
In the present work poly (N-vinyl-2-pyrrolidone-co-methyl methacrylate) copolymers were prepared successfully and cleanly by a one step process via cationic copolymerization of N-vinyl-2-pyrrolidone (NVP) with methyl methacrylate (MMA), in heterogeneous phase using “Maghnite-H+” (Mag-H+) as catalyst in bulk, Maghnite is a montmorillonite sheet silicate clay exchanged with protons to produce Maghnite-H+. Temperature is varied between 20 and 80 °C. The effects of reaction temperature, amount of Mag-H+ on the yield and the intrinsic viscosity (η) were investigated. A typical reaction product of poly (NVP-co- MMA) was analyzed by infra red spectroscopy (FTIR) and 1H-NMR, 13C-NMR spectroscopy as well as by viscosimetry. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)